Guide :

# The steps to solve; b + a = ab, solving for "a"?

My LCD is (ab), I am getting the incorrect answer of a = -b/1-b, the correct answer is a = b/1-b.  Please provide the steps, thank you.  tsj

## Research, Knowledge and Information :

284 quotes have been tagged as problem-solving: ... “If I had an hour to solve a problem I'd ... Instead, success requires making a hundred small steps go ...

### Algebra Word Problems Year 8 - solving word problems in ...

... by year 8 maths problem solving for 4 examples distance full ... 2 steps help unknown numbers algebra word problems year 8 ... steps using quot; ...

### Problem Quotes - BrainyQuote

Problem Quotes Loading... ... Worrying will not solve your problem. Joyce Meyer. Good, Alone, Busy. ... problem solving, ...

### Quotes on PROBLEM SOLVING - LeadershipNow.com

Quotes on PROBLEM SOLVING "The measure of success is not whether you have a tough problem to deal with, but whether it is the same problem you had last year."

### Problems and Problem Solving Quotes from Decision-Making ...

Process Steps; Decision ... Take a look at a select set of thought provoking and inspirational problems and problem solving quotes related to ... "To solve any ...

### How to Solve &quot;The Cube&quot; + Tips and Tricks For the ...

... How to Solve &quot; ... This step deals with permuting the corners and putting them in place ... i'M HAVING A PROBLEM IN SOLVING WEN THERE ARE SEVERAL HALF PLUS ...

### Mind Maps And Math Problem Solving - SlideShare

Mind Maps And Math Problem Solving ... Stages of problem solving, e.g. Polya's scheme from quot;How to Solve ... notation steps ...

### A B C 1. (3 points) Describe the following variables as ...

... Describe the following variables as quantitative or qualitative, ... View the step-by-step solution to: A B C 1. ... I need help solving these two questions ...

### Problems Quotes - BrainyQuote

Problems Quotes Loading... Problems ... You may not always have a comfortable life and you will not always be able to solve all of the world's problems at ...

### ITI 1121. Introduction to Computer Science II Laboratory 10 ...

... Part A: Solving two questions. Part B: Further understanding ... b)&quot;); test.Display (); test.Remove ... Here is a step-by-step approach for implementing the ...

## Suggested Questions And Answer :

### using the elimination method solve 6=6x+6y and -14y=18x+14

using the elimination method solve 6=6x+6y and -14y=18x+14 help me solve step by step 1) 6 = 6x + 6y 2) -14y = 18x + 14 Re-write equation 1: 3) 6x + 6y = 6 It is standard to have the unknowns of the left side of the equation. Now, for equation 2. -14y = 18x + 14 4) -18x - 14y = 14 Multiply equation 3 by 3. 3 * (6x + 6y) = 6 * 3 5) 18x + 18y = 18 Add equation 4 to equation 5.    18x + 18y = 18 +(-18x - 14y = 14) -------------------           4y = 32 You have just eliminated the x. Solve for y. 4y = 32 y = 8 You can used either equation 1 or equation 2 to solve for x. 1) 6 = 6x + 6y = 6    6x + 6(8) = 6    6x + 48 = 6    6x = 6 - 48    6x = -42    x = -7 Check it with equation 2. 2) -14y = 18x + 14    -14(8) = 18(-7) + 14    -112 = -126 + 14    -112 = -112 You have x = -7 and y = 8

### solve for x in this quadratic equation: 4x^2 + 5x = 6

Yes, sometimes factoring doesn't work. That's when we fall back on the quadratic formula. 4x^2 + 5x - 6 = 0 This is in the general form, y = ax^2 + bx + c. From that, we extract the values we need when we use the quadratic formula.        -b ± sqrt(b^2 - 4ac) x = --------------------------                2a        -5 ± sqrt(5^2 - 4(4)(-6)) x = -------------------------------                  2(4)        -5 ± sqrt(25 + 96) x = ------------------------                 8        -5 ± sqrt(121) x = --------------------               8        -5 ± 11 x = -----------           8        -5 + 11                       -5 - 11 x = -----------     and    x = -----------            8                                8        6                      -16 x = ---     and     x = ------       8                         8        3 x = ---     and     x = -2       4 Always check your answers. 4x^2 + 5x = 6 4(3/4)^2 + 5(3/4) = 6 4(9/16) + 15/4 = 6 9/4 + 15/4 = 6 24/4 = 6 6 = 6             That one checks. 4x^2 + 5x = 6 4(-2)^2 + 5(-2) = 6 4(4) - 10 = 6 16 - 10 = 6 6 = 6            That one checks, too. Answer: x = 3/4   and x = -2 The question was: solve for x in this quadratic equation: 4x^2 + 5x = 6 in this quadratic equation 4x^2 + 5x -6 = 0 how can I solve for x? How does it go step by step. I tried factoring, but got stuck because nothing made sense (2x +    )   (2x   -    )  = 0

### Dierdre's work to solve a math problem is shown below. Problem: How many 1 1/2- foot pieces can be cut from a 12-foot length of a ribbon?

Dierdre's work to solve a math problem is shown below. Problem: How many 1 1/2- foot pieces can be cut from a 12-foot length of a ribbon? Step 1: 1 1/2 divide by 12 = n Step 2: 3/2 divide by 12 = n Step 3: 3/2 X 1/12 = n Step 4: 3/24 = n Answer: 1/8 = n What was Dierdre's first error? A. She switched the divisor and the dividend in step 1 when creating an equation to model the problem. B. She used an improper fraction in step 2 that is not equivalent to 1 1/2. C. She replaced the divisor by its reciprocal in step 3 instead of re[;acing the dividend by its reciprocal. D. She reduced the fraction in step 4 incorrectly. Her first error was A. She switched the divisor and the dividend in step 1 when creating an equation to model the problem.

### how do you solve the equation x/4+5/12=3x/4-1/6

Take notice that each term in this equation is a fraction. Right that sucks! So we need to get rid of the fractions. It will make it a lot easier. The easiest way to do that is to multiply by a number that all of our denominators divide into. Called our least common denominator. So we have the numbers 4 , 12, 4 and 6. The smallest number that all of those numbers divide into is 12. So what I do is multiply all of my terms by 12. Now when multiplying a whole number by a fraction remember to put a one under your whole number and multiply across so for 12 times x/4 I will have 12*x/1*4 which leaves me 12x/4 which I can now divide the numbers to obtain 3x. Doing this for the rest of the problem I will obtain 3x + 5 = 9x - 2. I then need to use my steps for solving two step equations. Get the variable onto the same side and then use inverse operations to isoloate the variable. I show these steps in my videos located on my youtube channel http://www.youtube.com/mrbrianmclogan you can search for these types of problems and I work you through them step by step. Let me know if it helps

### how do you solve 6+x=20

How do you solve 6+x=20? Heres my equation example: 8 + X = 24 Your first step is to get X by itself. How do we do that? There is a positive 8 on the left hand side with the of the equals sign. Therfore subtract it out -8 + 8 = 0. What you do to the left side you MUST do to the right.  Now subtract 8 to the right hand side. 24 -8 = 16 This how it should look with all the steps above.... 8 + X = 24                     Original equation -8 + 8 + X = 24 -8         Add -8 to both sides X = 16                            Combine like terms on left. Solve on right.   CHECK with ORGINAL EQUATION 8 + X = 24     Original 8 + 16 = 24  ???  Substitute 16 with X. This is what we just solved. 24 = 24   Add 8 + 16 on left. 24 on right. Therfore X = 16

### Please solve this problem out for me it is Division! 45/4679 = ?

#1 is 0.00961743962

### How do solve for x ?2/3(4x-6)=3x+2

How do solve for x ?2/3(4x-6)=3x+2 I have to explain step by step in words after solving. 2/3(4x - 6) = 3x + 2 Multiply the terms inside the parentheses by 2/3 8/3 x - 4 = 3x + 2 Subtract 3x from both sides of the equation. 8/3 x - 4 - 3x = 3x + 2 - 3x 8/3 x - 3x - 4 = 2 Add 4 to both sides of the equation. 8/3 x - 3x - 4 + 4 = 2 + 4 8/3 x - 3x = 6 Convert the 3 in 3x to a fraction with 3 as the denominator. 8/3 x - 9/3 x = 6 Subtract the x terms. -1/3 x = 6 Multiply both sides of the equation by -3. (-1/3 x) * -3 = 6 * -3 x = -18 Check the answer. 2/3 * (4x - 6) = 3x + 2 2/3 * (4 * (-18) - 6) = 3 * (-18) + 2 2/3 * (-72 - 6) = -54 + 2 2/3 * (-78) = -52 -52 = -52

### how do I solve x/3 + 6 =3? Please give me the steps.

how do I solve x/3 + 6 =3? Please give me the steps. Please help me with this math problem. I'm not sure how of the steps to solving it. Thank you. x/3 + 6 = 3 x/3 + 6 - 6 = 3 - 6 x/3 = -3 x/3 * 3 = -3 * 3 x = -9

### how do you solve 2 step equations

solv step1, then put result intu step 2 normal: hav 2 dont-noz such as x & y step 1=solv for x step 2=plug this intu the x in equashun 2

### Need help understanding the process to solve sin^2x-cos(2x)= (-1/4)

Replace cos(2x) with 1-2sin^2(x) so that we have an equation with sine only. sin^2(x)-1+2sin^2(x)=-(1/4); 3sin^2(x)=1-(1/4)=3/4; sin^2(x)=1/4 (dividing through by 3); sin(x)=+1/2 so x=(pi)/6, 5(pi)/6, 7(pi)/6, 11(pi)/6 or 30, 150, 210, 330 degrees.